Ring Opening of Cyclic Sulfamidates with Magnesiated Heterocycles: Expedient Synthesis of Highly Functionalised Azaindolines and Azatetrahydroquinolines - Moss, Thomas A.; Hayter, Barry R.; Hollingsworth, Ian A.; Nowak, Thorsten (Synlett, 2012)
Magnesiated chloropyrimidine and chloropyridine derivatives, obtained by deprotonation with TMPMgCl⋅LiCl at room temperature, undergo facile ring-opening reactions with five- and six-membered N-Boc and N-Bn cyclic sulfamidates. After an acidic workup, the adducts undergo rapid intramolecular cyclisation on basification to give highly functionalised stereodefined azaindolines and azatetrahydroquinolines in good yields.
Keywords: cyclic sulfamidate; metalation; ring opening; pyrimidine; azaindoline